Best international practices in terms of the award of PPP projects and their comparison in Mexico, block I, 2017 - Gómez Monge, Rodrigo; Castro Coria, Eva Grissel (2021)
The study identifies, at a practical and normative level, whether there exist good international practices applied to bidding procedures, especially in the block I of the Program of Integral Strategy to Promote PPP Projects. To this effect, the guide Concessions for infrastructure was used, from which the ideal steps to carry out a bidding procedure were identified, the elements to be considered from each of them were extracted, the results were normalized in a scale from 0-1, and, finally, it was compared at a practical and at a normative level.